Improving Brand and Marketing Performance of SMEs Through Social Media Usage: An Empirical Research - Surya, Ade Permata; Muna, Nalal; Indriani, Farida (International Journal of Psychosocial Rehabilitation, 2020)
This study provides the role of social media usage to escalate competitive advantage, brand performance, and marketing performance among Indonesian SMEs. This study used a cross-sectional design with the purposive sampling method. Data were collected from a sample of 150 SMEs from the food, fashion, and cosmetics sector area by giving an online questionnaire to respondents through email. Partial least squares structural equation modeling was used to analyze the data with the helped of WarpPLS6.0. This study revealed that the model was able to explain 55% of the variance in SME marketing performance. Result showed that social media usage had a positive and significant effect on brand performance, competitive advantage and marketing performance. Moreover, SME brand performance was significantly positive give effect to marketing performance directly and indirectly with the mediating role of competitive advantage. Based on the results, theoretical and practical implications are provided for scholars and SME owners.